The science of writing characters : using psychology to create compelling fictional characters - Pelican, Kira-Anne (Bloomsbury Academic, 2021)
"Based on contemporary psychological research, The Science of Writing Characters provides writers with a completely new way of developing compelling and psychologically-credible fictional characters"- Resumé vydavatel
Terminologický slovník
Keywords: umělecká literatura; umělecká literatura -- psychologické aspekty; literární postavy; fiktivní postavy -- psychologické aspekty; tvůrčí psaní; typologie osobnosti; autorství literárních děl; filmová scenáristika; belles-lettres; belles-lettres -- psychological aspects; literary characters; fictitious characters -- psychological aspects; creative writing; typology (psychology); authorship of literary works; motion picture authorship; příručky; handbooks and manuals